Spatial microsimulation of household characteristics in Metro Manila identifying informal settlements and its implications to urban and housing policy - Tiglao, Noriel Christopher C. (2006)
Microsimulation modeling approach has recently become an accepted tool in the evaluation of economic and social policy. This method offers great potential in modeling complex urban systems in developing countries like the Philippines. In this article, the author adopted the above approach in estimating the magnitude and spatial distribution of informal households. InformalSim was presented and informal households are identified using direct measures - urban poverty and housing need. The article also explains the operational process for validating the model outputs using statistical small area estimation. Finally, the implications of spatial microsimulation in informing urban and housing policy were discussed.
Keywords: Squatter settlements -- Government policy -- Philippines; Squatter settlements -- Statistical methods; Urban poor -- Metro Manila